Analisis Spasial Kemiskinan di Pulau Jawa Tahun 2022 dengan Metode Geographically Weighted Regression (GWR) - Wisly Ryan Eliezer (Indonesian Journal of Applied Statistics, 2025)
Poverty is a multifaceted problem that poses a challenge for developing countries across the world, including Indonesia. Poverty is one of the global and national obligations stated in the first Sustainable Development Goals (SDGs), namely "Without Poverty". This study seeks to examine the factors that determine poverty in Java in 2022 while accounting for regional effects. Geographically Weighted Regression (GWR) is the methodology employed. The findings revealed that geographic/spatial characteristics had a substantial impact on poverty rates, and the GWR model generated a more accurate assessment measure than the global model. The structure of the parameters varies by location, with the variable coefficients of the health, salary, and credit indicators fluctuating, whilst the coefficients of the Education and Inflation Indicators remain similar throughout districts and cities. The government must implement proper measures to eliminate poverty not just nationally, but also in each district/city in Indonesia, particularly on Java Island. Policies might include improving human resources in education and health, monetary policies to sustain market pricing and determine minimum salaries, and policies to infuse credit assistance money into people's companies.Keywords: poverty, Geographically Weighted Regression (GWR), spatial analysis